Analyses of ultrasound-guided percutaneous pediatric kidney biopsy results: A single center experience - Damar, Cagri; Demircioglu Kilic, Beltinge (Annals of Medical Research, 2021)
Aim: Percutaneous pediatric kidney biopsies (KB) performed in our center for the past 5 years were evaluated retrospectively. The relationship was examined between histopathological results and variables such as age, gender and ethnicity (Turkish and Syrian children).Material and Methods: A total 330 ultrasound-guided percutaneous pediatric KBs were performed in our center between January 2015 and September 2019. The study included 318 pediatric patients comprising 152 females and 178 males with a mean age of 9.50 ± 4.89 years (range, 2 months- 18 years). Indications, results and complications of the KBs were retrospectively evaluated. Histopathological results were statistically compared between genders and three age groups (0-2, 2-12 and 12-18 years of age). Comparisons were made between the ethnicities and histopathological results.Results: The most common indication for KB was nephrotic syndrome (n: 220, 66.7%). In the biopsy results, the most common primary (n: 230, 69.7%) and secondary (n: 74, 22.4%) glomerular diseases were focal segmental glomerulosclerosis (n: 101, 30.6%) and Henoch-Schönlein purpura nephritis (n: 41, 12.4%), respectively. A statistically significant relationship was determined between the biopsy results and age and gender. No statistically significant relationship was observed between the biopsy results and ethnicity.Conclusion: KB is an important intervention for the identification of glomerular diseases, requiring appropriate treatment in children. The ethnic origin of the patients had no effect on the frequency of the type of the diseases.
Keywords: Childhood; glomerulonephritis; nephrotic syndrome; renal biopsy